Decrease of IL-1β and TNF in the Spinal Cord Mediates Analgesia Produced by Ankle Joint Mobilization in Complete Freund Adjuvant-Induced Inflammation Mice Model - Omura, Carlos Minoru; Lüdtke, Daniela Dero; Horewicz, Verônica Vargas; Fernandes, Paula Franson; Galassi, Taynah de Oliveira; Salgado, Afonso Shiguemi Inoue; Palandi, Juliete; Baldança, Heloiza dos Santos; Bittencourt, Edsel B.; Mack, Josiel Mileno; Seim, Lynsey A.; Martins, Daniel Fernandes; et al. (Frontiers in Physiology, 2022)
Objective: This study aims to investigate the effects of ankle joint mobilization (AJM) on mechanical hyperalgesia and peripheral and central inflammatory biomarkers after intraplantar (i.pl.) Complete Freund's Adjuvant (CFA)-induced inflammation. Methods: Male Swiss mice were randomly assigned to 3 groups (n = 7): Saline/Sham, CFA/Sham, and CFA/AJM. Five AJM sessions were carried out at 6, 24, 48, 72, and 96 hours after CFA injection. von Frey test was used to assess mechanical hyperalgesia. Tissues from paw skin, paw muscle and spinal cord were collected to measure pro-inflammatory (TNF, IL-1β) and anti-inflammatory cytokines (IL-4, IL-10, and TGF-β1) by ELISA. The macrophage phenotype at the inflammation site was evaluated by Western blotting assay using the Nitric Oxide Synthase 2 (NOS 2) and Arginase-1 immunocontent to identify M1 and M2 macrophages, respectively. Results: Our results confirm a consistent analgesic effect of AJM following the second treatment session. AJM did not change cytokines levels at the inflammatory site, although it promoted a reduction in M2 macrophages. Also, there was a reduction in the levels of pro-inflammatory cytokines IL-1β and TNF in the spinal cord. Conclusion: Taken together, the results confirm the anti-hyperalgesic effect of AJM and suggest a central neuroimmunomodulatory effect in a model of persistent inflammation targeting the pro-inflammatory cytokines IL-1β and TNF.